Lower Rate of Daily Smokers With Symptomatic COVID-19: A Monocentric Self-Report of Smoking Habit Study - Miyara, Makoto; Tubach, Florence; Pourcher, Valérie; Morélot-Panzini, Capucine; Pernet, Julie; Haroche, Julien; Lebbah, Said; Morawiec, Elise; Gorochov, Guy; Caumes, Eric; Hausfater, Pierre; Combes, Alain; et al. (Frontiers in Medicine, 2022)
Background: Identification of prognostic factors in COVID-19 remains a global challenge. The role of smoking is still controversial. Methods: PCR-positive in- and outpatients with symptomatic COVID-19 from a large French University hospital were systematically interviewed for their smoking status, use of e-cigarette, and nicotinic substitutes. The rates of daily smokers in in- and outpatients were compared using the same smoking habit questionnaire to those in the 2019 French general population, after standardisation for sex and age. Results: The inpatient group was composed of 340 patients, median age of 66 years: 203 men (59.7%) and 137 women (40.3%), median age of both 66 years, with a rate of 4.1% daily smokers (CI 95% [2.3–6.9]) (5.4% of men and 2.2% of women). The outpatient group was composed of 139 patients, median age of 44 years: 62 men (44.6%, median age of 43 years) and 77 women (55.4%, median age of 44 years). The daily smoker rate was 6.1% (CI 95% [2.7–11.6], 5.1% of men and 6.8% of women). Amongst inpatients, daily smokers represented 2.2 and 3.4% of the 45 dead patients and of the 29 patients transferred to ICU, respectively. The rate of daily smokers was significantly lower in patients with symptomatic COVID-19, as compared to that in the French general population after standardisation by age and sex, with standardised incidence ratios (SIRs) of 0.24 [0.12–0.48] for outpatients and 0.24 [0.14–0.40] for inpatients. Conclusions: Daily smoker rate in patients with symptomatic COVID-19 is lower as compared to the French general population